Covid-19 Pandemic and Regional Inequalities in The U.S. - Duran, Hasan Engin (Contemporary Business and Economic Issues II, 2023)
Purpose of this chapter is to search the effect of Covid-19 pandemic on the income inequalities across US states. Our dataset covers 51 US states over the period 1997-2021. The variable analyzed is the per capita real GDP (y). Having applied, Kolmogorov-Smirnov and Kernel Density Estimations, we reached several results. Covid-19 had a diverse impact on the states, while in almost half of the states, there is tightening of the economy, in the others, it is observed positive economic growth between 2019 and 2021. The covid-19 pandemic did not influence significantly the state level income distribution and inequalities.